THE ROLE OF THE NATIONAL IDEA IN THE FORMATION OF A PERFECT PERSON IN THE NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
This article analyzes the role of national ideology in shaping a well-rounded individual in the context of New Uzbekistan. It explores the historical roots of the concept of a well-rounded person, its significance in contemporary society, and its connection to national ideology. The paper also discusses the role of education, spirituality, and social institutions in this process and provides conclusions regarding future directions.